ENGLISH PROFICIENCY OF THAI UNDERGRADUATE STUDENTS USING CEFR IN KHONKAEN - Phong-a-ran, Nathaporn; Supaweena Luksup , Supaweena Luksup; Chaisoda, Pornpalin (Journal of Buddhist Education and Research (JBER), 2019)
The purposes of this study were to (1) study the English proficiency of Thai students referencing Common European Framework of Reference for Languages (CEFR) by using online placement test and (2) study the differences and similarities of problems which were found in the placement test.The research instruments were an online English placement test and an interview. The population of this study were from 200 undergraduate students who enrolled in the test in 2018 academic year. The participants were 100 students and 6 of them were randomly selected for the interview. The 6 students consist of three students with good grade of English and three students with poor grade of English. The statistics used in this study were percentage, average, and standard deviation.It was found that average of English proficiency level of the participants referencing CEFR was A1.